Synthesis and Antibacterial Evaluation for Some New Schiff-bases Derived from P-aminoacetanilide (Baghdad Science Journal, 2023)
Derivatives of Schiff-bases possess a great importance in pharmaceutical chemistry. They can be used for synthesizing different types of bioactive compounds. In this paper, derivatives of new Schiff bases have been synthesized from several serial steps. The acid (I) was synthesized from the reaction of dichloroethanoic acid with 2 moles of p-aminoacetanilide. New acid (I) converted to its ester (II) via the reaction of (I) with dimethyl sulphate in the present of anhydrous of sodium carbonate and dry acetone. Acid hydrazide (III) has been synthesized by adding 80% of hydrazine hydrate  to the new ester using ethanol as a solvent. The last step included the preparation of new Schiff-bases (IV-VIII) by the reaction of acid hydrazide with appropriate aromatic aldehydes and using glacial acetic acid as a catalyst. New derivatives were diagnosed by FT-IR, and by mass and 1HNMR spectroscopy (some of them). Derivatives (IV-VIII) were screened for their antibacterial against E. Coli (G-) and staph. aureus (G+). All tested compounds were found to have activity against the two kinds of bacteria.